Control of maximum water age based on total chlorine decay in secondary water supply system. (January 2022) - Geng, Bing; Fan, Jingjing; Shi, Minghao; Zhang, Shuai; Li, Jiuling
Abstract: 97% of residential buildings are installed with secondary water supply system (SWSS) in China. In order to meet the water pressure demand, the SWSS has become a key solution to store and transport drinking water. The water age of the SWSS directly determines the quality of tap water, while total chlorine is a key indicator to evaluate the quality and safety of the water supply network. This study revealed the relationship between total chlorine and water age controlled by adjusting the liquid level of the secondary water supply tank. Models governing water age and the total chlorine concentration were developed based on the variation of the liquid level and the attenuation rate of the total chlorine in the SWSS. Furthermore, the validation was performed through case studies. The developed models can gain effective insights for determining the longest water age while guaranteeing the concentration of total chlorine meets the demand of the lower standard in SWSS. The secondary chlorine dosage would be quantified and added to the pipe network. The integration of the SWSS would be guided by water age in some old communities. The taste of tap water for direct drinking water could be improved by adjusting of water age using this model. The optimization method is easy to use for identifying efficient solutions for SWSS operation. Graphical abstract: Image 1 Highlights: Relationship between total chlorine and water age under liquid level was revealed. A model governing water age and the total chlorine concentration was developed. The longest water age was quantified to meet demand of chlorine concentration. The model could improve direct drinking water taste by adjusting water age.